2021
DOI: 10.1177/03611981211020005
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of 4-D System Fundamental Diagram in Urban Air Mobility Traffic Flow

Abstract: Urban air mobility (UAM) is an emerging mode that promises to provide relief to congested urban streets. UAM relies on airspace, however, which is an exhaustible resource considering minimum aircraft separation requirements. In light of these requirements and UAM vehicle attributes, a simulation is developed to explore UAM traffic flows and congestion development. A decentralized conflict resolution scheme is employed in the form of a non-linear program (NLP) to offer improved flexibility in detours relative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
(21 reference statements)
1
13
0
Order By: Relevance
“…The air traffic flow results from each scenario are analyzed graphically in four relationships, with each using aircraft density as the independent variable. Density was used because it has been identified in previous research ( 8 , 9 , 23 ) as a driving factor in airspace congestion and flow breakdown. The other four air traffic flow measures (conflicts, average actual speed, average effective speed, and effective flow rate) are used as the dependent variables.…”
Section: Simulated Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The air traffic flow results from each scenario are analyzed graphically in four relationships, with each using aircraft density as the independent variable. Density was used because it has been identified in previous research ( 8 , 9 , 23 ) as a driving factor in airspace congestion and flow breakdown. The other four air traffic flow measures (conflicts, average actual speed, average effective speed, and effective flow rate) are used as the dependent variables.…”
Section: Simulated Resultsmentioning
confidence: 99%
“…There is also a limited set of work in studying macroscopic air traffic flow patterns. Cummings and Mahmassani ( 8 ) developed and used a simulator of AAM vehicles to measure air traffic flow with aircraft densities, speeds, and flow rates. With these measurements the authors identified familiar patterns of traffic congestion such as declining vehicle speeds because of density and a system fundamental diagram pattern relating density and flow rate.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations